Weed density affected by different soil management and fertilization systems - Balbinot Junior, Alvadi Antonio; Veiga, Milton da (Revista de Ciências Agroveterinárias, 2014)
The objective of this work was to evaluate monocotyledonous and dicotyledonous weed  density from seventh to tenth years of trial in five systems of soil and fertilization management, in  Campos Novos, SC, Brazil. The experimental  design was longitudinal and transverse rows  in blocks, with three replications. The soil  management systems were: no tillage; chisel plow + single secondary disk harrowing; primary and double secondary disking (conventional tillage); conventional tillage with crop residues burned; and conventional tillage with crop residue removal. The fertilization strategies used were: no fertilization (control); recommended soluble fertilizers; poultry litter; cattle slurry; and swine slurry. The winter cover crops used from seventh to tenth years were: rye; common vetch; black oat and multi-cropping between black oat and common vetch. There was an increasing of monocotyledonous weed density with the increase of mechanical disturbance and the absence of straw in soil. On the other hand, there was increase of dicotyledonous weed density with decreasing of mechanical disturbance and maintaining of straw in the soil. No expressive difference in weed density occurred among the fertilization systems.